How Moving Together Brings Us Together: When Coordinated Rhythmic Movement Affects Cooperation - Cross, Liam; Wilson, Andrew D.; Golonka, Sabrina (Frontiers in Psychology, 2016)
Although it is well established that rhythmically coordinating with a social partner can increase cooperation, it is as yet unclear when and why intentional coordination has such effects. We distinguish three dimensions along which explanations might vary. First, pro-social effects might require in-phase synchrony or simply coordination. Second, the effects of rhythmic movements on cooperation might be direct or mediated by an intervening variable. Third, the pro-social effects might occur in proportion to the quality of the coordination, or occur once some threshold amount of coordination has occurred. We report an experiment and two follow-ups which sought to identify which classes of models are required to account for the positive effects of coordinated rhythmic movement on cooperation. Across the studies, we found evidence 1) that coordination, and not just synchrony, can have pro-social consequences (so long as the social nature of the task is perceived), 2) that the effects of intentional coordination are direct, not mediated and 3) that the degree of the coordination did not predict the degree of cooperation. The fact of inter-personal coordinating (moving together in time and in a social context) is all that’s required for pro-social effects. We suggest that future research should use the kind of carefully controllable experimental task used here to continue to develop explanations for when and why coordination affects pro-social behaviours.